2021
DOI: 10.1007/s10867-020-09562-5
|View full text |Cite
|
Sign up to set email alerts
|

Relative humidity in droplet and airborne transmission of disease

Abstract: A large number of infectious diseases are transmitted by respiratory droplets. How long these droplets persist in the air, how far they can travel, and how long the pathogens they might carry survive are all decisive factors for the spread of droplet-borne diseases. The subject is extremely multifaceted and its aspects range across different disciplines, yet most of them have only seldom been considered in the physics community. In this review, we discuss the physical principles that govern the fate of respira… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 214 publications
(209 reference statements)
2
67
0
Order By: Relevance
“…Thus, we hypothesize that the water droplets at the high end of the percentage relative humidity that we studied would also be a more potent bactericide and virucide. This conjecture is consistent with the observations presented elsewhere that viruses are effectively killed in small water droplets when the relative humidity is in the range of 40% to 60% but survive much better when the relative humidity is less than 40% or greater than 60% (Lin and Marr, 2020;Birks and Rowlen, 2020;Božič and Kanduč, 2021). Although not without some controversy (Heneghan et al, 2021;Greenhalgh et al, 2021;Niazi et al,2021), it does seem well established that viral respiratory diseases are primarily transmitted by airborne droplets.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, we hypothesize that the water droplets at the high end of the percentage relative humidity that we studied would also be a more potent bactericide and virucide. This conjecture is consistent with the observations presented elsewhere that viruses are effectively killed in small water droplets when the relative humidity is in the range of 40% to 60% but survive much better when the relative humidity is less than 40% or greater than 60% (Lin and Marr, 2020;Birks and Rowlen, 2020;Božič and Kanduč, 2021). Although not without some controversy (Heneghan et al, 2021;Greenhalgh et al, 2021;Niazi et al,2021), it does seem well established that viral respiratory diseases are primarily transmitted by airborne droplets.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…All droplets formed from the mist maker are believed to start with the same H 2 O 2 concentration but then undergo evaporation at different rates depending on the relative humidity, The rate of evaporation depends on many factors and has been reviewed elsewhere (Božič and Kanduč, 2021). H 2 O 2 becomes increasingly concentrated in the remaining water droplet (Hultman et al, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…RH and temperature are also main environmental factors that can affect the stability and viability of a virus in air. Previous studies suggested that non-enveloped viruses are able to survive longer at high RHs (70 to 90%) while enveloped viruses survive longer at low RHs (<30%) ( Božič and Kanduč, 2021 ); however, these observations are not always consistent. Moreover, enveloped viruses are observed to be more stable at low temperature and susceptible to damage at high temperature due to dysfunction of their phospholipid bilayers ( Price et al, 2019 ).…”
Section: Basics Of Airborne Pathogenic Virusesmentioning
confidence: 91%